2019
DOI: 10.3126/ajms.v10i3.22505
|View full text |Cite
|
Sign up to set email alerts
|

Serum Reproductive hormone levels in male symptomatic HIV/AIDS patients on Antiretroviral therapy negative to Malaria parasite in Nnewi, Anambra State, Nigeria

Abstract: Background: AIDS is an endemic disease that causes death among young adults worldwide especially in Nigeria. Aims and Objectives: This study investigated the serum reproductive hormone levels in symptomatic HIV/AIDS male subjects on ART who are negative to malaria parasite in Nnewi, Anambra State, Nigeria. Materials and Methods: A total of 274 adult male participants aged between 18 and 60 years were randomly recruited, and grouped into: symptomatic HIV (stage 11) infected male participants on ART … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…This is similar to previous studies carried out in a south-eastern state of Nigeria in 2021, which reported significantly higher AE in HIV-positive patients compared to HIV-negative persons. 39 Similar to our finding, Ezeugwunne et al 40 in 2019 reported a reduction in serum concentration of AE as the length of ART treatment progressed among HIV-positive patients in Nnawi, Nigeria. The reason for reduced AE with increased length of treatment is unclear but may be related to the immune system.…”
Section: Discussionsupporting
confidence: 86%
“…This is similar to previous studies carried out in a south-eastern state of Nigeria in 2021, which reported significantly higher AE in HIV-positive patients compared to HIV-negative persons. 39 Similar to our finding, Ezeugwunne et al 40 in 2019 reported a reduction in serum concentration of AE as the length of ART treatment progressed among HIV-positive patients in Nnawi, Nigeria. The reason for reduced AE with increased length of treatment is unclear but may be related to the immune system.…”
Section: Discussionsupporting
confidence: 86%
“…Also earlier reports have shown occurrence of abnormal androgen metabolism which resulted in increased aromatization of testosterone to estradiol in HIV infected men [ 27 ]. A study by Ezeugwunne et al [ 28 ]., confirmed this fact. In contrast to the previous study [ 28 ], the present study showed decreased estradiol level among ART naïve HIV infected males as compared with negative control but the difference was not statistically significance.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Ezeugwunne et al [ 28 ]., confirmed this fact. In contrast to the previous study [ 28 ], the present study showed decreased estradiol level among ART naïve HIV infected males as compared with negative control but the difference was not statistically significance.…”
Section: Discussionmentioning
confidence: 99%